2001
DOI: 10.1021/jp010490x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Uptake of Gaseous N2O5by (NH4)2SO4, NH4HSO4, and H2SO4Aerosols

Abstract: The heterogeneous uptake of gaseous N 2 O 5 by ammonium sulfate [(NH 4 ) 2 SO 4 ], ammonium bisulfate [NH 4 HSO 4 ], and sulfuric acid [H 2 SO 4 ] aerosols as a function of relative humidity has been investigated at room temperature and atmospheric pressure. Ammonium-containing aerosols were generated by a constantoutput atomizer and conditioned by passing through a diffusion dryer. Sulfuric acid aerosols were produced by the homogeneous reaction of SO 3 and H 2 O in a borosilicate vessel. Addition of a dry or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
138
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(150 citation statements)
references
References 23 publications
12
138
0
Order By: Relevance
“…Additionally the particle chemistry, and furthermore hygroscopic properties, are affected by aqueous phase reactions taking place in liquid particles (e.g. Kane et al, 2001;Volkamer et al, 2009). Findings by Buchholz et al (2009) suggest that secondary organics generated in sunny conditions are more hygroscopic and also more CCN active than those generated under cloudy conditions.…”
Section: Hygroscopic Growth Factorsmentioning
confidence: 99%
“…Additionally the particle chemistry, and furthermore hygroscopic properties, are affected by aqueous phase reactions taking place in liquid particles (e.g. Kane et al, 2001;Volkamer et al, 2009). Findings by Buchholz et al (2009) suggest that secondary organics generated in sunny conditions are more hygroscopic and also more CCN active than those generated under cloudy conditions.…”
Section: Hygroscopic Growth Factorsmentioning
confidence: 99%
“…For instance, the total gas-to-particle transfer rate of N 2 O 5 K N 2 O 5 is calculated as the sum of the specific K N 2 O 5 ,i x as follows: [29] We implemented the reactions of HO 2 , NO 2 , NO 3 on wet aerosol particles (e.g., all the soluble modes (NS, KS, AS, and CS) in the model, independently of their composition) with the uptake coefficients of 0.2, 10 À4 and 10 À3 , respectively, following Jacob [2000]. The uptake of N 2 O 5 on aerosol particles follows Evans and Jacob [2005] and Liao and Seinfeld [2005], i.e., different coefficients are used for sulfate [Kane et al, 2001;Hallquist et al, 2003], organic carbon [Thornton et al, 2003], black carbon [Sander et al, 2003], sea salt [Atkinson et al, 2004], and mineral dust [Bauer et al, 2004]. The O 3 uptake coefficient on mineral dust is set to 10 À5 following Bauer et al [2004].…”
Section: Heterogeneous Chemistrymentioning
confidence: 99%
“…Recently, Morgan et al (2015) demonstrated that this influence of chloride may not be represented properly, and the "high" O : C regime defined in Gaston et al (2014) was scarcely observed over north-western Europe by airborne regional measurements. Several laboratory studies reported that γ N 2 O 5 substantially varies with temperature, RH, and particle composition (Mentel et al, 1999;Kane et al, 2001;Hallquist et al, 2003;Chang et al, 2011;Brown and Stutz, 2012;Gaston et al, 2014). Davis et al (2008) developed a parameterization scheme (Davis08) of γ N 2 O 5 for aerosols containing nitrate, sulfate, and ammonium.…”
Section: Introductionmentioning
confidence: 99%
“…Davis et al (2008) developed a parameterization scheme (Davis08) of γ N 2 O 5 for aerosols containing nitrate, sulfate, and ammonium. It was developed on the basis of numerous previous laboratory studies (Badger et al, 2006;Folkers et al, 2003;Hallquist et al, 2003;Folkers, 2002;Kane et al, 2001;Hu and Abbatt, 1997;Mozurkewich and Calvert, 1988) with respect to temperature, RH, and particle compositions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation